Implementasi Pembelajaran Bahasa Arab Berbasis Teks dalam Keterampilan Menulis Berdasarkan Perspektif Hammond - Syukur, Hasan; Amalia, Nabila Nailil; Mulyanti, Titi; Taufiqurrochman, R (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Arabic has a level of complexity in terms of rules, meaning, and vocabulary which causes students to find it difficult to learn and even avoid learning Arabic, one of which is writing skills. This research aims to provide an overview and describe how to apply the text-based Arabic language learning model in writing skills through a theoretical review according to Hammond. This research method uses a qualitative approach with descriptive research type with data collection techniques, that is interviews, observation, and documentation. The data analysis model used is the Miles Huberman and Saldana interactive model including data condensation, data display, and conclusion drawing. The results of this research are text-based learning in students' writing skills at Ma'had Sabilillah Malang using Hammound's text-based learning model with 4 stages, namely: Stage 1; BKOF (Building knowledge of the field), Stage 2; MOT (Modelling of text), Stage 3; JCOT (Join Construction of text), Stage 4; ICOT (Independent Construction of Text) is the implementation of students' knowledge and understanding to produce text independently. In its implementation, it starts with teacher-centered learning (Teacher-centered approach) then teachers and students collaborate to play an active role in compiling and analyzing texts that have been created with themes about daily activities. In the final stage, students learn independently and the teacher only acts as controlling. The Arabic language learning process based on Hammond's theory creates a classroom atmosphere where writing skills are not as usual, which is tense and quickly gets boring, resulting in students synergizing with each other in producing their best work in writing